Rating positioning as part of Polish and Ukrainian Universities comparative aspect - Yusiuk, Oksana; Maslova, Yuliia; Zukow, Walery (Journal of Education, Health and Sport, 2018)
In the article ranking positioning as part of Polish and Ukrainian universities in comparative perspective. In particular, the analysis of rating positions reputable universities in the world rankings QS EECA University Rankings and Webometrics ranking of world’s universities.